2015
DOI: 10.3892/mmr.2015.4459
|View full text |Cite|
|
Sign up to set email alerts
|

Chloride intracellular channel 1 regulates migration and invasion in gastric cancer by triggering the ROS-mediated p38 MAPK signaling pathway

Abstract: Chloride intracellular channel 1 (CLIC1) has been demonstrated to be overexpressed in gastric cancer, and elevated CLIC1 expression levels are markedly associated with the processes of tumor cell migration and invasion. However, the regulatory mechanism and signaling pathway underlying these processes have remained to be elucidated. The present study examined the impact of N-acetyl cysteine (NAC), indanyloxyacetic acid (IAA)-94 and SB203580, inhibitors of reactive oxygen species (ROS), as well as CLIC1 and p38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In previous studies, the overexpression of c‐myc was positively related to high proliferation activity, and the overexpression and gene amplifications of Myc family members were found in brain tumors . A previous study confirmed that the p38 mitogen‐activated protein kinase (MAPK) signaling pathway was associated with the cellular processes of cell migration and invasion of gastric cancer, and the inhibition of this signaling pathway could potentially result in the restraining of cell migration and invasion . From the aforementioned findings and studies, it was indicated both the p38 MAPK signaling pathway as well as miR‐494 made a great difference in tumor progression.…”
Section: Introductionmentioning
confidence: 90%
“…In previous studies, the overexpression of c‐myc was positively related to high proliferation activity, and the overexpression and gene amplifications of Myc family members were found in brain tumors . A previous study confirmed that the p38 mitogen‐activated protein kinase (MAPK) signaling pathway was associated with the cellular processes of cell migration and invasion of gastric cancer, and the inhibition of this signaling pathway could potentially result in the restraining of cell migration and invasion . From the aforementioned findings and studies, it was indicated both the p38 MAPK signaling pathway as well as miR‐494 made a great difference in tumor progression.…”
Section: Introductionmentioning
confidence: 90%
“…Viral proteins modulate cellular ion channel functionality to favor their life cycles ( 2 ). In recent years, Cl − channels have emerged as some of the most active cellular ion channels during tumorigenesis, because of their involvement in both cell motility and proliferation ( 17 , 18 ). We reasoned that Cl − channels could therefore play a role in MCPyV ST-induced cell motility.…”
Section: Resultsmentioning
confidence: 99%
“…A key question remains, how does MCPyV ST target CLIC1 and CLIC4, and how does this ultimately benefit the virus? Both channels are widely expressed and their activity regulates components of the cytoskeleton, adhesion molecules, and cell signaling pathways ( 18 , 27 , 30 ), all of which may contribute to MCPyV ST tumor formation. We observed that the MCPyV ST effects on CLIC1/CLIC4 did not occur at the transcriptional level, ruling out the involvement of known MCPyV ST cellular targets including p53 and tumor necrosis factor α (TNFα) ( 31 33 ) that regulate CLIC transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…At low or endurable levels, ROS may aid cancer progression either by playing as signaling elements or by stimulating alterations in genomic DNA or DNA damage. For example, ROS can promote expression of cyclin D1, phosphorylation of extracellular signal-regulated kinase (ERK) and JUN N-terminal kinase (JNK), and activation of mitogen-activated protein kinase (MAPK), all of which are connected to cancer progression and survival [ 260 , 261 , 262 , 263 , 264 , 265 ]. Moreover, ROS have been found to inversely incapacitate tumor suppressors, including protein tyrosine phosphatases (PTPs) and phosphatase and tensin homolog (PTEN), due to the existence of the redox-sensitive cysteine residues that exist in their catalytic sites [ 266 , 267 , 268 ].…”
Section: The Association Between Oxidative Stress and Cancer Progrmentioning
confidence: 99%